Pepsin Hydrolysate from Surimi Industry-Related Olive Flounder Head Byproducts Attenuates LPS-Induced Inflammation and Oxidative Stress in RAW 264.7 Macrophages and In Vivo Zebrafish Model - H. H. A. C. K. Jayawardhana; N. M. Liyanage; D. P. Nagahawatta; Hyo-Geun Lee; You-Jin Jeon; Sang In Kang (Marine Drugs, 2023)
Fish head byproducts derived from surimi processing contribute about 15% of the total body weight, which are beneficial to health because they contain essential nutrients. In this study, olive flounder (OF) was the target species in order to maximize the byproduct utilization. In RAW 264.7 macrophages, the seven hydrolysates from OF head byproducts were examined for their inhibitory potential against inflammation and the oxidative stress induced by lipopolysaccharides (LPS). The pepsin hydrolysate (OFH–PH) demonstrated strong anti-inflammatory activity via the down-regulation of NO production, with an IC50 value of 299.82 ± 4.18 µg/mL. We evaluated the inhibitory potential of pro-inflammatory cytokines and PGE2 to confirm these findings. Additionally, iNOS and COX-2 protein expressions were confirmed using western blotting. Furthermore, the results from the in vivo zebrafish model demonstrated that OFH–PH decreased the LPS-elevated heart rate, NO production, cell death, and intracellular ROS level, while increasing the survival percentage. Hence, the obtained results of this study serve as a platform for future research and provide insight into the mediation of inflammatory disorders. These results suggest that OFH–PH has the potential to be utilized as a nutraceutical and functional food ingredient.